Pemberdayaan Pendidikan Taman Pendidikan Al-Qur’an Di Dusun Kalangan Desa Mojoseto Kecamatan Gondang Kabupaten Nganjuk - Yusuf, Muhammad; Kholik, Kusnul; Mustaqim, Ahmad; Munir, M.; Ma’sum, Toha (Janaka, Jurnal Pengabdian Masyarakat, 2018)
Kalangan, a village in Mojoseto, is part of the Gondang sub-district, Nganjuk Regency, which is located in the north, close to Sukomoro District. The condition of rural communities is very thick with the tradition of mutual cooperation and togetherness that is still going well. Economic conditions that are included in the middle and lower are one of the causes of the level of education and knowledge that are also not yet developed, including their religious insights. TPA At-taubah, one of the Islamic education institutions managed by the community as an asset. In the implementation of education, constrained human resources that have not been fulfilled, including infrastructure, organizational structure, and operational permits. Through the community service program of the Nganjuk STAIDA lecturer which requires a contribution of thought and direct involvement in helping to solve these problems. With the touch and plunge directly, it is expected to be able to explore and develop the potential that exists for the progress of religious programs in the community. With cooperation and utilizing the existing potential, the service program can run smoothly and meet the needs of infrastructure, and management of operational permits